PENGARUH TRUST DISPOSITION DAN RISK AVERSION TERHADAP NIAT BELI ONLINE PADA FJBKASKUS DI WILAYAH SURABAYA - SEPTIONO MUHIBUDDIEN, ALI (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:The continued development of technology to make the consumer more and more ways to pull through buying and selling. Kaskus trading forum is the first forum that offers services to sell or buy Online. Formulation of the problem used is whether the Trust Disposition and Risk aversion affect Intention to Buy Online either partially (individually) or simultaneously (together) .Penelitian has a total sample of 390 respondents. Respondents were FJB site visitors Kaskus.Uji classical assumptions used are lnormalitas test, hereroskedasitas test and multicollinearity test. The results of this study showed 76.2% of independent variables, namely the Trust Disposition and Risk aversion affect the dependent variable Intention to Buy Online. Keywords:trust disposition, Risk aversion, and intention to buy Online